ChemInform Abstract: 1, 3‐Carbon D—A Strategy for [3 + 2] Cycloadditions/Annulations with Imines: Synthesis of Functionalized Pyrrolidines and Related Alkaloids. Issue 35 (2nd September 2014) - Kumar, Indresh
Abstract Review: [48 refs.